Tracking mechanical and morphological dynamics of regenerating Hydra tissue fragments using a two fingered micro-robotic hand - Veschgini, Mariam; Gebert, Florian; Holstein, Thomas W. (Applied physics letters, 2016)
Regeneration of a tissue fragment of freshwater polyp Hydra is accompanied by significant morphological fluctuations, suggesting the generation of active forces. In this study, we utilized a two fingered micro-robotic hand to gain insights into the mechanics of regenerating tissues. Taking advantage of a high force sensitivity (∼1 nN) of our micro-hand, we non-invasively acquired the bulk elastic modulus of tissues by keeping the strain levels low (ε < 0.15). Moreover, by keeping the strain at a constant level, we monitored the stress relaxation of the Hydra tissue and determined both viscous modulus and elastic modulus simultaneously, following a simple Maxwell model. We further investigated the correlation between the frequency of force fluctuation and that of morphological fluctuation by monitoring one “tweezed” tissue and the other “intact” tissue at the same time. The obtained results clearly indicated that the magnitude and periodicity of the changes in force and shape are directly correlated, confi...
Gesehen am 14.02.2017